Ultrasound Assisted Extraction (UAE) of Macroalgae Padina australis From Tidung Island, Indonesia and Testing Its Antibacterial Activity - Yosepin, Elpina; Panjaitan, Riong Seulina; Purwati, Purwati (BIOEDUKASI, 2024)
Padina australis is one of brown macroalgae that grows in Indonesian ocean. This study aimed to determine the optimum of time extraction of Padina australis ethanolic extract extracted by Ultrasound Assisted Extraction (UAE) method, its phytochemical compounds and the antibacterial activity of Padina australis ethanolic extract against on four different pathogenic bacteria (Salmonella typhii, Shigella sonnei, Escherichia coli dan Bacillus cereus). Padina australis were extracted by Ultrasound Assisted Extraction (UAE) method using ethanol solvent (70%) with three different times (10, 20 and 30 minutes). The ethanolic extract of Padina australis were evaluated its antibacterial activity and its minimal inhibitory concentration (MIC) by using disc diffusion method. The results showed that the optimum UAE time of Padina australis was 20 minutes which yielded 0.4%. Moreover, the ethanolic extract of Padina australis contained alkaloids, saponins, flavonoids, tannins, steroids, and terpenoids. Furthermore, this study indicates that Padina australis ethanolic extract demonstrated its antibacterial activity against all bacteria tested. MICs of Padina australis ethanolic extract determined for S. typhi and B. cereus were at 6.25 ppm and for S. sonnei was at 12,5 ppm. Whereas, this extract showed the MIC at 25 ppm on E. coli.